Impact of Cartoons in Hindi Language on Religious Knowledge: A Trend Study of Social Learning in School-Going Children (5–7 Years) in Lahore, Pakistan - ZIA, ANJUM; NAZ, IRAM; MUNIR, MOHSINA (Islamic Studies, 2017)
This trend study examines the impact of cartoons in Hindi language on religious knowledge of children in Lahore, Pakistan. Specific objectives of the study are to explore the habits of watching Hindi language cartoons, religious knowledge (Hinduism and Islam) and influence of Hindu content of the cartoons on religious beliefs of Pakistani Muslim children. The study applied survey method and used a questionnaire as tool of data collection. Since this was a trend study, data was collected in 2010 and 2015. Universe of the study was private schools of Lahore with sample size of 200 children of 5 to 7 years who studied in classes 1–3 and viewed selected cartoons through cable television. The theoretical framework of this research is based on Social Learning Theory. The results of this study reveal that majority of the children are regular viewers of targeted cartoons and aware of Hindu religious beliefs and values. Such cartoons in Hindi language influence religious knowledge of Pakistani Muslim children in terms of beliefs, ethics, and Islamic values.